Right ventricular marginal branch occlusion after blunt force trauma to the chest. (April 2016) - Jadhav, Nikhil; Gupta, Pritha; Press, Marcella Calfon
Coronary artery occlusion following a blunt trauma is a rare complication. We report a case of a 56-year-old man who experienced an intermediate code trauma following a motor vehicle accident. The patient had a visible 'seat-belt sign' and complained of chest pain. Initial electrocardiogram showed mild ST segment elevation accompanied by elevation of cardiac enzymes. Echocardiogram and cardiac magnetic resonance imaging were consistent with right ventricular systolic dysfunction. Coronary angiogram revealed 100% occlusion of proximal right ventricular marginal branch. The patient was managed medically. This case presents a rare case of right ventricular marginal occlusion following blunt chest trauma.